2015
DOI: 10.1080/09853111.2015.1046354
|View full text |Cite
|
Sign up to set email alerts
|

Interpretation of gravity anomalies to delineate some structural features of Biga and Gelibolu peninsulas, and their surroundings (north-west Turkey)

Abstract: On the basis of gravity data, derived anomaly traces were presented for the interpretation of some shallow structural features of Biga and Gelibolu peninsulas. Since building general understanding of subtle details about subsurface geology is of great importance considering that the study area is tectonically important, some advanced data processing techniques were implemented to gravity anomalies in a detailed manner. The procedures were performed using a MATLABbased software package (Gravity and Magnetic Int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 67 publications
(26 citation statements)
references
References 84 publications
0
21
1
4
Order By: Relevance
“…Hence, depending on the objectives of analyses and studies, many processing techniques have been reported for interpreting potential field anomalies. If potential field data quality permits, numerous analysing procedures can be conducted that facilitate in building a general understanding of the details of causative bodies (Ekinci and Yiğitbaş 2012 , 2015 ; Balkaya et al 2012 ; Ekinci et al 2013 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hence, depending on the objectives of analyses and studies, many processing techniques have been reported for interpreting potential field anomalies. If potential field data quality permits, numerous analysing procedures can be conducted that facilitate in building a general understanding of the details of causative bodies (Ekinci and Yiğitbaş 2012 , 2015 ; Balkaya et al 2012 ; Ekinci et al 2013 , 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…The subtle details in the potential field anomaly maps can be made more visible through some derivative based filters (Ekinci and Yigitbas, 2012and 2015, Ekinci et al 2013. Many boundary detection filters have been proposed to determine the boundaries of potential field sources.…”
Section: Derivative Methodsmentioning
confidence: 99%
“…where F is the magnetic field, f and f −1 are the Fourier and inverse Fourier transforms, respectively and |k| is the radial wave number. Here n is the order of the vertical derivative (Blakely 1995;Ekinci et al 2013;Ekinci and Yigitbaş 2015). Figure 6 shows the first vertical derivative (FVD) map of the RTP-TMI of the study area.…”
Section: Vertical Derivatives (Vd)mentioning
confidence: 99%